Assimilation of Yb defect states in ZnO: Structural, optical and magnetic investigations. (September 2020) - Sharma, Dhirendra Kumar; Varshney, Mayora; Shukla, Sweta; Sharma, Kapil Kumar; Kumar, Vipin; Sharma, Anuradha
Abstract: Magnetic ordering in the non-ferromagnetic substances (like; ZnO) is intriguing and could be more interesting to investigate if other defect states are incorporated by the non-magnetic ion doping. We have investigated the effect of Yb doping on the structural, morphology, optical and magnetic properties of ZnO. Different Yb concentrations were applied to prepare the solid solution of Zn1-x Ybx O (with x = 0.00, 0.01 and 0.05) using the co-precipitation route. X-ray diffraction (XRD), energy-dispersive X-ray spectroscopy (EDX), high resolution scanning electron microscope (HR-SEM), UV–visible spectroscopy and vibrating sample magnetometer (VSM) have been employed to characterize the samples. Amalgamation of Yb in ZnO has manifested the lower angle shifting of XRD peaks and consequently increased lattice parameters of ZnO are observed. UV–visible absorption spectroscopy investigations have established the net decrease in the optical band gap energy of ZnO as a function of Yb defect levels in the compound. HR-SEM study revealed that the insertion of Yb ions in ZnO could transform the spherical structures into agglomerated non-spherical structures. The magnetic measurements have revealed the diamagnetic ordering in the pure ZnO, which ultimately transformed into ferromagnetic ordering via incorporation of Yb defect states. Highlights: A simple co-precipitation technique was used to prepare pure and Yb doped ZnO structures. The XRD patterns of pure and Yb doped ZnO samples revealed that all samples are single crystalline phase of hexagonal structure. A red shift was observed in the absorption spectra of pure and Yb doped ZnO samples. The room temperature ferromagnetism has been examined in 1 and 5 atm. % Yb doped ZnO structures.